2017
DOI: 10.1101/162198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chill coma in the locust,Locusta migratoria, is initiated by spreading depolarization in the central nervous system

Abstract: The ability of chill-sensitive insects to function at low temperatures limits their geographic ranges. They have species-specific temperatures below which movements become uncoordinated prior to entering a reversible state of neuromuscular paralysis. In spite of decades of research, which in recent years has focused on muscle function, the role of neural mechanisms in determining chill coma is unknown. Spreading depolarization (SD) is a phenomenon that causes a shutdown of neural function in the integrating ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…We also hypothesized that the cell membrane and ion transport could be important selection targets, especially relating to calcium and potassium ion balance (Cooper, Hammad, & Montooth, ; Findsen, Overgaard, & Pedersen, ; Overgaard & MacMillan, ; Parker et al, ; Teets, Yi, Lee, & Denlinger, ). Challenges to neural and muscular systems from low temperatures can result from inactivation of voltage‐sensitive calcium channels, which drive the action potential upstroke in insect muscle (Andersen et al, ; Findsen et al, ), as well as changes in extracellular potassium that spreads depolarization across cell membranes (Robertson et al, ). Therefore, adaptations to modulate the effects of ion channel thermal sensitivity may be critical to the maintenance of neuromuscular function across environmental temperatures within a species range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also hypothesized that the cell membrane and ion transport could be important selection targets, especially relating to calcium and potassium ion balance (Cooper, Hammad, & Montooth, ; Findsen, Overgaard, & Pedersen, ; Overgaard & MacMillan, ; Parker et al, ; Teets, Yi, Lee, & Denlinger, ). Challenges to neural and muscular systems from low temperatures can result from inactivation of voltage‐sensitive calcium channels, which drive the action potential upstroke in insect muscle (Andersen et al, ; Findsen et al, ), as well as changes in extracellular potassium that spreads depolarization across cell membranes (Robertson et al, ). Therefore, adaptations to modulate the effects of ion channel thermal sensitivity may be critical to the maintenance of neuromuscular function across environmental temperatures within a species range.…”
Section: Discussionmentioning
confidence: 99%
“…Genes relating to thoracic muscle function are probably targets of selection from temperature variation across species ranges, as muscles are important both for flight and shivering thermogenesis in Bombus (Heinrich, ; Heinrich & Kammer, ; Hosler, Burns, & Esch, ). Genes related to the nervous system are generally important for maintaining activity at temperature extremes (Robertson, Spong, & Srithiphaphirom, ), with those involved in neuromuscular function obvious candidates because of the importance of flight muscle (Esch & Goller, ; Goller & Esch, ; Kammer & Heinrich, ; MacMillan et al, ). Finally, loss of nerve and muscle excitability at temperature extremes, especially cold, is associated with failure of membrane channels to maintain ion homeostasis, so ion channel genes are also likely candidates (Andersen, MacMillan, & Overgaard, ; Overgaard & MacMillan, ; Robertson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 Indeed, multiple studies have shown beneficial properties of SD, including preconditioning, upregulation of growth factors, and neurogenesisis. [72][73][74][75][76][77] In addition, previous studies in insects [78][79][80][81] and rodents 72,73,82,83 suggest that SD may play a neuroprotective role during ischemia. 1,84 It is possible that this protection is enabled by a "neuronal silencing" mechanism associated with SD 85 wherein metabolism is quickly shut down, possibly to conserve residual energy and minimize production of reactive oxygen species, potentially leading to an improved survival and outcome in reversible processes.…”
Section: Discussionmentioning
confidence: 99%
“…Spreading depolarisation is triggered by failure 74 to maintain ion gradients between the intra-and extracellular compartments within the CNS, which results in 75 depolarization of neurons and glial cells and a surge of potassium ions in the extracellular space of the brain, 76 preventing neural activity (Robertson, 2004;Robertson et al (submitted); Spong et al, 2016). Furthermore, 77 studies have shown that inter-and intraspecific differences in cold coma are highly correlated with the loss 78 of CNS function in insects Robertson et al, 2017). Given the similarity in the 79 behavioural phenotypes of heat and cold coma there is an obvious possibility that the onset of heat coma is 80 also caused by CNS failure in insects.…”
Section: Introduction 34mentioning
confidence: 99%